2021
DOI: 10.3389/fgene.2021.790888
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine Regulator-Mediated Immune Genes Identify Breast Cancer Immune Subtypes and Predict Immunotherapy Efficacy

Abstract: Breast cancer (BRCA) is a heterogeneous malignancy closely related to the tumor microenvironment (TME) cell infiltration. N6-methyladenosine (m6A) modification of mRNA plays a crucial regulator in regulating the immune microenvironment of BRCA. Immunotherapy represents a paradigm shift in BRCA treatment; however, lack of an appropriate approach for treatment evaluation is a significant issue in this field. In this study, we attempted to establish a prognostic signature of BRCA based on m6A-related immune genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…M 6 A modification has been proposed to be participated in cardiovascular physiological and pathological processes [ [18] , [19] , [20] ]. However, the vital roles of m 6 A writer METTL3 in high glucose exposure vascular endothelial cells are unknown [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…M 6 A modification has been proposed to be participated in cardiovascular physiological and pathological processes [ [18] , [19] , [20] ]. However, the vital roles of m 6 A writer METTL3 in high glucose exposure vascular endothelial cells are unknown [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using a bioinformatics approach, present study was performed to conduct the genome-wide comparison of HCC [20,21]. Moreover, the prediction tools indicated that there were remarkable m 6 A modi ed sites on AFAP1-AS1 RNA sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of m6A modification mediated by METTL3 and METTL14 was demonstrated to connect with immune system and tumor microenvironment through increasing the production of cytokines and chemokines including IFN-γ, CXCL9, and CXCL10, accompanied by an enhanced response to immunotherapy (L. immune evasion (Tallima et al, 2021). It was demonstrated that m6A modification is associated with the expression of MHC-related antigenpresenting molecules, such as human leukocyte antigen (HLA) (M. M. Zhang et al, 2021). This suggests that there is a potential immune escape mechanism, which is involved by m6A modification.…”
Section: Involvement Of M6a Modification In Neoplastic Immunity Of Im...mentioning
confidence: 99%
“…Major histocompatibility complex (MHC) Class I protein expresses on the surface of tumor cells, and the defection of MHC Class I leads to immune evasion (Tallima et al, 2021). It was demonstrated that m6A modification is associated with the expression of MHC‐related antigen‐presenting molecules, such as human leukocyte antigen (HLA) (M. M. Zhang et al, 2021). This suggests that there is a potential immune escape mechanism, which is involved by m6A modification.…”
Section: M6a Modification‐regulated Neoplastic Immunity and Tumorigen...mentioning
confidence: 99%